Determination of Employee Performance: Analysis of Self-Efficacy, Work Motivation and Work Environment (Garment in Indonesia) - Didin Sjarifudin; Ni Nyoman Sawitri (International Journal of Psychology and Health Science, 2023)
The purpose of the study is to provide an overview and prove qualitative results from scientific articles related to variables to the garment industry, especially managers and supervisors, the research method used is qualitative with a review of scientific articles in proving research results, while the research results exist The influence between self-efficacy and employee performance, there is an influence between work motivation and employee performance, there is also an influence between the work environment and employee performance, these results provide evidence that the three variables above have an influence on employee performance, this is a reference for managers and supervisors in the garment industry in making decisions related to needs in the company. The results of this research or study are important for qualitative, quantitative, and mixed methods research with differentiating variables used with different research objects.